Efeito neuroprotetor da condroitinase ABC e células tronco mesenquimais no traumatismo medular agudo experimental em ratos - Tatiana Malagoli Taguchi (2014)
Acute spinal cord trauma is frequent in veterinary clinical routine, and sometimes determines the patient euthanasia, or serious damage to the life's quality, as the loss of motor function. Glial scar is considered a barrier to the spinal cord regeneration, and it is constituted by chondroitin sufate proteoglycan production by reactive atrocytes. On this study 25 rats were submitted to the compressive spinal cord trauma, and lately treated with chondroitinase ABC intramedullary imediately after trauma, and mesenchymal stem cells from adipose tissue intravenously threehours later. The groups that received chondroitinase, associated or not to stem cells, presented better motor recovery than those that were not treated with the enzyme. These animals also had increase in the relative gene expression, evaluated by real-time PCR of BDNF and PECAM-1 in relation to the control group. The expression of vimentin was also evaluated, and chondroitinase alone and stem cell associated groups, as well as the stem cell group, had lower expression when compared with the control group, suggesting that chondroitinase intramedullary, applied immediately after the trauma, is capable of promoting early functional recovery and inducing the production of neuroprotective factors. In addition, the enzyme and stem cells modulate astrogliosis, reducing the expression of vimentin, a component of the intermediate flares present in the glial scar.